Artificial Intelligence (AI) News Anchor: How AI’s Performance in Journalistic Sector? - Tira Nur Fitria (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
This research reviews Artificial Intelligence (AI) news anchors in the journalistic sector. This research uses library research. The analysis shows that the rise of the AI news anchor/newsreaders marked a milestone in journalism. However, at the same time, it also sparked discussion and concern. In April 2023, one of Indonesia's private television stations, TvOne, introduced several news anchors alias AI news anchors, named Sasya and Nadira, and Bhoomi later. Several news agencies and media in various countries have previously demonstrated innovation with AI newsreaders such as China, South Korea, Russia, Kuwait, and India. The appearances of male and female AI newsreaders are presented to resemble the human appearance and given data that can be read using text-to-speech technology. The emergence of AI anchors has presented traditional announcers and presenters with new opportunities and challenges. Therefore, it is necessary to confront the formidable obstacles that AI anchors present to presenters. AI's application to the AI news anchor allows AI technologies to give a synthesized voice and digitally manipulated visage based on developer-supplied content. However, AI technology is still immature, and its adoption in the media faces numerous obstacles. Future AI news anchor trends may include interactive broadcasting and effective news anchors. Various jobs may be represented by robots with AI. AI may be able to replace the work of human journalists and even replace humans as news presenters. However, we need to understand that AI is cannot a substitute for humans, but it is a tool that can help improve human performance.